Alginates in therapy for gastroesophageal reflux disease - V G Avdeev (Терапевтический архив, 2015)
This article presents evidence of the prevalence of gastroesophageal reflux disease (GERD) and highlights its main treatment options. Among its medications, particular emphasis is laid on alginates and their main mechanisms of action are described. There is information on the efficacy of alginates, including the alginate-antacid Gaviscon Double Action, in treating GERD. Recommendations for how to administer these drugs are given.